Kinetoplastid membrane protein-11 as a vaccine candidate and a virulence factor in Leishmania - Mendonça, Sergio Coutinho Furtado de (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunoparasitologia. Rio de Janeiro, RJ, Brasil.